2017
DOI: 10.1162/jocn_a_01143
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Hippocampal versus Frontoparietal Network Contributions to Retrieval and Memory-guided Exploration

Abstract: Memory can profoundly influence new learning, presumably because memory optimizes exploration of to-be-learned material. Although hippocampus and frontoparietal networks have been implicated in memory-guided exploration, their specific and interactive roles have not been identified. We examined eye movements during fMRI scanning to identify neural correlates of the influences of memory retrieval on exploration and learning. Following retrieval of one object in a multi-object array, viewing was strategically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…Although extensive research has documented the binding and comparison functions of the hippocampus during memory-guided behavior, research using eye movement monitoring suggests that these functions extend to active viewing behavior. As discussed earlier, the hippocampus supports the formation of lasting memories via encoding-related visual exploration [13,[15][16][17][18], and retrieval of those memories by means of memory-guided overt visual attention [93]. Extending these findings to gaze reinstatement, Ryals, Wang, Polnaszek, and Voss (2015) looked at the similarity of eye movements ("exploration overlap") during study and test for novel and configurally-similar computer-generated scenes.…”
Section: What Are the Neural Correlates Of Gaze Reinstatement?mentioning
confidence: 86%
“…Although extensive research has documented the binding and comparison functions of the hippocampus during memory-guided behavior, research using eye movement monitoring suggests that these functions extend to active viewing behavior. As discussed earlier, the hippocampus supports the formation of lasting memories via encoding-related visual exploration [13,[15][16][17][18], and retrieval of those memories by means of memory-guided overt visual attention [93]. Extending these findings to gaze reinstatement, Ryals, Wang, Polnaszek, and Voss (2015) looked at the similarity of eye movements ("exploration overlap") during study and test for novel and configurally-similar computer-generated scenes.…”
Section: What Are the Neural Correlates Of Gaze Reinstatement?mentioning
confidence: 86%
“…Indeed, exploratory viewing enhances subsequent memory [10, 4043], and hippocampal damage impairs viewing during memory formation [39]. This suggests that exploratory viewing is an integral part of the hippocampal-dependent memory formation process, rather than a mere by-product.…”
Section: Hippocampal Contributions To Exploratory Viewing For Memory mentioning
confidence: 99%
“…These memory-exploration interactions are likely bidirectional and normally occur in rapid iteration during memory formation, making them incredibly difficult to isolate using methods with low temporal resolution such as fMRI. Nonetheless, we recently segregated brief-delay memory retrieval from ensuing exploration using an artificially imposed delay period [61]. In doing so, we were able to distinguish hippocampal activity associated with short-delay memory retrieval from fronto-parietal activity associated with specific memory-related viewing patterns during subsequent exploration.…”
Section: Hippocampal Contributions To Exploratory Viewing For Memory mentioning
confidence: 99%
“…Similarly, across repeated viewings of configurations in a contextual cuing task in which a target had to be located among distractors, Manelis and Reder demonstrated that increased hippocampal activity predicted decreases in the number of fixations needed to locate the target. Activity in the hippocampus has also been shown to vary with activity in the frontoparietal visual attention network that, in turn, was related to strategic visual exploration during an active memory retrieval task …”
Section: Neuroimagingmentioning
confidence: 99%
“…Activity in the hippocampus has also been shown to vary with activity in the frontoparietal visual attention network that, in turn, was related to strategic visual exploration during an active memory retrieval task. 94 More recently, neuroimaging studies have shown that oculomotor behavior modulates neural activity in the hippocampus during perceptual processing, or encoding; thus, the relationship between oculomotor behavior and hippocampal activity is not just observed in tasks in which memory retrieval is required. Using simultaneous eye tracking-fMRI recordings and a scene encoding task, Henderson and Choi 95 showed that the duration of gaze fixations was negatively related to activity strength in the hippocampus.…”
Section: Neuroimagingmentioning
confidence: 99%